Clinical outcomes of takotsubo syndrome in patients with cancer: a systematic review and meta-analysis - Osawa, Takumi; Tajiri, Kazuko; Ieda, Masaki; Ishizu, Tomoko (Frontiers in Cardiovascular Medicine, 2023)
Background: Recent studies suggested a relationship between Takotsubo syndrome (TTS) and malignancy. However, clinical outcomes of TTS associated with cancer have not been assessed completely. This study was aimed to investigate the outcomes of patients with TTS and cancer.We performed a systematic review and meta-analysis to evaluate the clinical outcomes of TTS in patients with and without malignancy. We systematically reviewed and analyzed 14 studies (189,210 patients) published in PubMed and Cochrane Library databases until December 2022. The primary outcome was all-cause mortality at the longest follow-up.The prevalence of current or previous malignancy in patients with TTS was 8.7% (16,461 patients). Patients with TTS and malignancy demonstrated a higher risk of mortality at the longest follow-up than those with TTS alone (odds ratio [OR], 2.41; 95% confidence interval [CI]; 1.95-2.98; P<0.001). Moreover, cancer was significantly associated with an increased risk of in-hospital or 30-day mortality (